Expanded Percussion Notation in Recent Works by Cat Hope, Stuart James and Lindsay Vickery. Issue 1 (4th March 2017) - Vickery, Lindsay; Devenish, Louise; James, Stuart; Hope, Cat
Abstract : This paper discusses the percussion notation of Western Australian composers Lindsay Vickery, Stuart James and Cat Hope. Both the compositional and performative aspects of their notational conventions are considered in the diverse approaches they take to the specification of timbre, improvisation, and ensemble coordination. The design and interpretation of screen-based technologies, tablature gestural approaches and spectrographic notation is explored using Lindsay Vickery's The Miracle of the Rose (2015) InterXection (2002) and Lyrebird (2014), Cat Hope's Broken Approach (2014), Sub Aerial (2015), and Tone Being (2016) and Stuart James' Kinabuhi | Kamatayon (2015) as case studies.